Quadratic voting: How mechanism design can radicalize democracy - Lalley, Steven P.; Weyl, E. Glen (AEA Papers and Proceedings, 2018)
Can mechanism design save democracy? We propose a simple design that offers a chance: individuals pay for as many votes as they wish using a number of “voice credits” quadratic in the votes they buy. Only quadratic cost induces marginal costs linear in votes purchased and thus welfare optimality if individuals' valuation of votes is proportional to their value of changing the outcome. A variety of analysis and evidence suggests that this still-nascent mechanism has significant promise to robustly correct the failure of existing democracies to incorporate intensity of preference and knowledge.